The Stagnation of Employment. (Monthly Review: An Independent Socialist Magazine, 2004)
Part of a special issue on the stagnation of employment. An examination of the stagnation of employment in the U.S. labor market in 2004 and of the “missing jobs” in the economy is presented. This stagnation is not simply the result of normal business cycle fluctuations, it has been caused by deeper, structural changes in the capitalist economy. Moreover, the U.S. economy is now experiencing a structural shift of national and global dimensions that may entail a long-term decrease in employment. Employment stagnation is so incorporated into the structure of accumulation that there is no easy way out for the modern capitalist economy; efforts to solve the problem by intensifying exploitation globally have only succeeded in aggravating the underlying malaise; and the legitimacy of the system is being undermined in the mind of the broader population, which is likely to have political and economic consequences.